2004
DOI: 10.1007/s11103-004-2142-6
|View full text |Cite
|
Sign up to set email alerts
|

Targets of the WRKY53 transcription factor and its role during leaf senescence in Arabidopsis

Abstract: Arabidopsis WRKY proteins comprise a family of plant specific zinc-finger-type transcription factors involved in the regulation of gene expression during pathogen defense, wounding, trichome development, and senescence. To understand the regulatory role of the senescence-related WRKY53 factor, we identified target genes of this transcription factor by a pull down assay using genomic DNA and recombinant WRKY53 protein. We isolated a number of candidate target genes including other transcription factors, also of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
389
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(397 citation statements)
references
References 47 publications
7
389
0
1
Order By: Relevance
“…Especially, the second reason seems to be important, because under the low light conditions used in the present study A. thaliana, ecotype Columbia 0 develops higher number of enlarged leaves. Applying gel activity staining methods, an increase in the chloroplastic SOD activity and a fourfold decrease in the APX activity were observed during the developmental transition to bolting and flowering (Ye et al 2000) leading to an increase of H 2 O 2 content at that time point (Miao et al 2004). Unfortunately, APXs are extremely unstable enzymes, i.e., only two isoforms, APX1 and probably APX2, can be visualized by activity staining in native PAGE (Mittler and Zilinskas 1993; Panchuk et al 2002), whereas other isoenzymes loose their activity during isolation procedure and subsequent electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the second reason seems to be important, because under the low light conditions used in the present study A. thaliana, ecotype Columbia 0 develops higher number of enlarged leaves. Applying gel activity staining methods, an increase in the chloroplastic SOD activity and a fourfold decrease in the APX activity were observed during the developmental transition to bolting and flowering (Ye et al 2000) leading to an increase of H 2 O 2 content at that time point (Miao et al 2004). Unfortunately, APXs are extremely unstable enzymes, i.e., only two isoforms, APX1 and probably APX2, can be visualized by activity staining in native PAGE (Mittler and Zilinskas 1993; Panchuk et al 2002), whereas other isoenzymes loose their activity during isolation procedure and subsequent electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that AtWRKY53 expression can be induced by pathogen attack, hydrogen peroxide and salicylic acid (SA) (Miao et al 2004;Miao and Zentgraf 2007;Murray et al 2007). To further clarify the potential functions of WRKY53, we examined its expression profiles more precisely.…”
Section: Expression Patterns Of Atwrky53mentioning
confidence: 99%
“…It has previously been reported that AtWRKY53 expression can be induced by exogenous H 2 O 2 , which in turn aids the regulation of cellular redox and ROS homeostasis by directly promoting the expression of catalase (Miao et al 2004). To further confirm the effect of AtWRKY53 on H 2 O 2 levels in guard cells through the regulation of catalase expression, we determined the expression level of the three catalase genes, CAT1 (AT1G20630), CAT2 (AT1G58030) and CAT3 (AT1G20620), under drought conditions in the Col-0 and 53OV lines (Fig.…”
Section: Atwrky53 Up-regulates the Expression Of Cat1 And Cat2 Under mentioning
confidence: 99%
See 1 more Smart Citation
“…WRKY53 is upregulated at a very early stage but transcripts decrease again over time, implying that the gene plays a regulatory role in early senescence events (Hinderhofer and Zentgraf, 2001). A knockout line of WRKY53 shows delayed senescence, while inducible overexpression causes precocious senescence, evidence that it functions as a positive element (Miao et al, 2004). Identification of the direct target genes for WRKY53 should further reveal the regulatory pathways for WRKY53-mediated senescence.…”
Section: Other Regulatory Genesmentioning
confidence: 99%